PENGARUH PROGRAM BANK SAMPAH ZAKAT COMMUNITY DEVELOPMENT TERHADAP KESEJAHTERAAN MUSTAHIK (Studi Pada Kampung Kandang, Kota Bekasi) - Azizah, Anisa Nur; Muttaqin, Aminnullah Achmad (Islamic Economics and finance in Focus, 2022)
Indonesia as a developing country still has a lot to improve to be able to compete with other countries, one of which is alleviating poverty. Poverty can be defined as the inability to access basic rights such as education, health, and inequality in income distribution. Bekasi City is a developed city, but on the other hand Bekasi City has a high poverty rate as well. One way to maximize poverty alleviation is to use ZIS funds. Bekasi City BAZNAS as the institution authorized to manage ZIS funds has a community empowerment program, namely the ZCD waste bank program. This research was conducted in Kampung Kandang with the aim of examining the effect of the ZCD waste bank program on the welfare of mustahik. The research approach method used is quantitative and the data used are primary data by distributing questionnaires. This study uses SPSS 23 statistical analysis. This study analyzes the effect of the participation of waste bank customers, training or mentoring, waste weighing, and waste savings on the welfare of mustahik. The results of this study indicate that all the variables used, consisting of waste bank customer participation (X1), training/assistance (X2), waste weighing (X3), and waste savings (X4) have a simultaneous and positive effect. Where the waste bank customer participation variable (X1) has a t value of 4.065 and training/assistance (X2) has a t value of 3.547 which is a significant variable. While the waste weighing variable (X3) has a t value of 1.331 and the waste saving variable (X4) has a t value of -1,600 which is an insignificant variable.